A study of changes in various echocardiographic parameters in patients with chronic stable angina undergoing percutaneous coronary intervention (PCI) - Hossain, Muhammad Mobarock; Rahman, AKM Fazlur; Siddique, Md Abu; Banerjee, Sajal Krishna; Ahmed, Chowdhury Meskat; Hoque, Harisul; Rahman, Mohammad Abdur; Mohammad, Noor; Joarder, Ariful Islam; Khaled, Fakhrul Islam; Kabir, Mohammad Faisal Ibn; Ahsan, Syed Ali (University Heart Journal, 2015)
PCI has been used increasingly for revascularization in ischemic heart disease patients. In the cardiology practice, the assessment of left ventricular (LV) function is of paramount importance. Two-dimensional echocardiography and Doppler echocardiography remain the most important diagnostic tests/tool for the evaluation of left ventricular function. The present study was conducted to determine the impact of PCI on myocardial function assessed by 2D, M mode and tissue Doppler echocardiography in patients with chronic stable angina. The interventional study was carried out in the Department of Cardiology, University Cardiac Centre, Bangabandhu Sheikh Mujib Medical University Hospital, Dhaka over a period of 1 year between January 2013 to December 2013. Patients with chronic stable angina undergoing percutaneous coronary intervention (PCI) during the study period were the study population. A total of 40 such patients were consecutively included in the study. The myocardial function parameters were assessed by 2D, M mode and Tissue Doppler echocardiography before PCI and 48 hours and 6 weeks after PCI. Left ventricular end diastolic dimension (LVEDD) did not experience any change 2 days after PCI, but a significant reduction was noted 6 weeks after PCI (P < 0.001). Similarly no change was observed 48 hours after PCI in left ventricular end systolic dimension (LVESD) but a significant decrease was evident 6 weeks after PCI (p < 0.001). LVEF also did not exhibit any change in the first 2 days after PCI, but significantly raised 6 weeks after PCI (p < 0.001). Tissue Doppler Imaging (TDI) showed that there was insignificant improvement in Em, Am, and Em/ Am ratio 48 hours after PCI. But there was significant improvement of the same parameters at the lateral mitral annulus 6 weeks after PCI (p = 0.044, p = 0.036 and p = 0.021 respectively). While DTm did not experience any change in first 2 days after PCI, it exhibited significant change at endpoint of study (p = 0.018), RTm and Sm peak velocity however, did not improve following PCI. Q-wave increased from 7.0 cm/sec before PCI to 7.2 cm/ sec 48 hours after PCI and 7.5 cm 6 weeks after PCI (p < 0.001). Percentage of strain decreased from -15.0 before PCI to -15.4 at the endpoint (p < 0.001) and strain rate from -1.3% before PCI to -1.4% 6 at the endpoint. From the findings of the study it can be concluded that Tissue Doppler echocardiographic indices Strain, strain rate and Q analysis can detect the early changes of improvement in the left ventricular myocardium in patient with chronic stable angina after 48 hours of PCI . Other 2D , M mode and tissue Doppler echocardiographic indices showed improvement after 6 weeks of PCI. University Heart Journal Vol. 9, No. 2, July 2013; 99-106